Enterococcus faecalis endocarditis in an immunocompetent patient: a case report - Mejía Angel, July Vanessa (2024)
Infective endocarditis is a disease characterized by inflammation of the endocardium secondary to the entry of pathogens into the circulation, which may include bacteria, fungi and even viruses. Its etiology may vary among microorganisms; however, Enterococcus faecalis bacteria is the third most frequent, after S. aureus and S. pyogenes. For each of these causative agents of the disease, it is necessary to assess the appropriate treatment aimed at eradicating the microorganism, based on the international guidelines of the European Society of Cardiology (ESC), institutional parameters and local epidemiology. We present the case of a 44-year-old man of African descent with no comorbidities, whose only significant history includes dental procedures in the context of Enterococcus faecalis infective endocarditis. With this case, we aim to give visibility to the causative microorganism and the clinical picture for which the patient consulted, highlighting pathognomonic and non-pathognomonic clinical signs of the disease. It is also important to emphasize the need to promptly initiate antibiotic therapy, suspect the disease, exclude multiple differential diagnoses and perform early surgical management, as all of these can influence the prognosis and outcome of the patient, with death being the most serious of these. Likewise, we intend to provide guidance to healthcare professionals who may face similar cases. Finally, we would like to emphasize to emphasize the importance of effective communication between institutions, as there may be delays due to transfers, the need to repeat paraclinical and imaging test to confirm the diagnosis, and delays in surgical management due to a lack of necessary resources, which can lead to the worsening of the disease.